The difference maker making your attitude your greatest asset - Maxwell, John C. (Nashville Nelson Business, 2006)
What can make the difference in your life today? How can twopeople with the same skills and abilities, in the same situation, end up withtwo totally different outcomes? Leadership expert John C. Maxwell says thedifference maker is attitude. For those who have ever wondered what may beseparating them from achieving the kind of personal and professional successthey've always dreamt of, Dr. Maxwell has some words of insight: "Your attitudecolors every aspect of your life. It is like the mind's paintbrush."
Includes bibliographical references (p. [179]-182).
Keywords: Attitude (Psychology)